Pemberdayaan unit Center of Excellence Fakultas Farmasi UNHAS melalui produksi produk inovatif minuman instan Ginger Creamy Plus - Sartini, Sartini; Djide, Nana Juniarti Natsir; Nainu, Firzan; Amir, Muhammad Nur; Mangilep, Muhammad Agung Ady (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
One of the key performance indicators (KPI/IKU) of the Ministry of Higher Education and Science and Technology is IKU 5: community recognition of lecturers' research outcomes. The PPUPIK-UNHAS community service program aimed to promote lecturers' innovative products for broader public recognition. In this community service initiative, we introduced an instant ginger-based beverage (Zingiber officinale), developed by modifying the traditional Sarabba drink with bee pollen. Ginger is well known for its health benefits, including antioxidant properties, improved digestion, pain and inflammation relief, enhanced immunity, and preventing nausea and vomiting. Including bee pollen—rich in amino acids, flavonoids, B vitamins, and minerals—further enhances the drink's functional health effects. The resulting product, Ginger Creamy Plus, was formulated as an instant drink, with each sachet containing 1.2 g of ginger and 0.3 g of bee pollen. This innovation has been registered with HAKI under the simple patent category and has received a P-IRT business permit. It is expected to be commercialized on an industrial scale in collaboration with UNHAS business units and registered with the Food and Drug Supervisory Agency.